Fitting and testing roll-over protective structures on self-propelled agricultural machinery - Domenico Pessina (Journal of Agricultural Engineering, 2013)
Roll-Over Protective Structure (ROPS) represents the state of art for the driver’s protection in case of tractors roll-over. Despite their real risk of overturning, the ROPS approach for the Self-Propelled agricultural Machinery (SPM) is quite recent. Due to the several SPM categories available on the market, characterized by very different mass, dimension and working functions, the fitting of a ROPS and consequently the ascertainment of its protection level is quite complicated. SPM could be preliminarily divided into at least two categories: - large SPM: combine, forage, potato, sugar-beet and grape harvesters; sprayer; etc.; - small SPM: ride-on tractor, mower, comb side-delivery rake, etc. The most followed approach at present is to check preliminarily the overturning behavior of the SPM considering its longitudinal and lateral stability; if a real risk of overturning is ascertained, in order to minimize the likelihood of driver’s injury the manufacturer often installs a ROPS. The consequent need is to provide some test criteria of them. Sprayers between large SPM, and comb side-delivery rake between small SPM were the machine types on which ROPS were tested, adopting in both cases the procedure provided by Code 4 issued by the Organization for Economic and Cooperation Development (OECD), dedicated to ROPS fitted on conventional agricultural and forestry tractors. Notwithstanding the very different dimensions of these two SPM, this standard was selected considering the predictable roll-over behavior, also in relation with the front and rear track values. On the 4950 kg mass sprayer was fitted a closed cab, while on the 690 kg mass comb side-delivery rakes a 3-pillars frame was applied. In both cases the response of the tests was positive, so indicating a general suitability of OECD Code 4 to assure a ROPS good driver’s protection level in case of overturning. On the other hand, to ascertain more in detail the roll-over behavior of the SPM, some further questions need to be deeply examined, such as the driver’s place location, the height of the centre of gravity from the ground in different machine configurations (i.e. with crop tanks empty or full), the external silhouette, the axles mass distribution of the laden/unladen machine, etc.